Craniella quirimure sp. nov. from the mangroves of Bahia (Brazil) (Tetillidae, Spirophorida, Demospongiae) - Peixinho, Solange; Cosme, Bruno; Hajdu, Eduardo (Zootaxa, 2005)
Craniella quirimure sp. nov. is fully described here on the basis of dozens of specimens collected between 1975 and 2004 from Bahia, Brazil. The species is the only warm shallow-water, mangrove species of Craniella in the Tropical Atlantic with cortical oxeas up to 1000 µm long and 28 µm thick, two categories of protriaenes, anatriaenes which can be larger than 9000 µm and sigmaspires smaller than 15 µm.